Kontrak Kerja: Analisis Hukum dan Implementasi - Muhammad Iqbal Rifai; Yopa Emalia Fajarini; Reinhard Silaen; Bambang Fitrianto (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the legal aspects and implementation of employment contracts in Indonesia in the context of changes in labor regulations. The study analyzes the legal framework underlying employment contracts, worker rights protection, employer obligations, and implementation challenges in the field. Using a qualitative approach and legal document analysis, this study identifies several key issues related to employment contracts, including imbalance in bargaining power, unclear clauses, and compliance with the latest regulations. The results of the study show that although there has been progress in legal protection through labor laws, implementation in the field still faces various challenges. This study provides recommendations for improving policies and practices related to employment contracts that are more balanced, transparent, and in line with the principle of fairness for all parties.